Communication in a Human biomonitoring study: Focus group work, public engagement and lessons learnt in 17 European countries - Exley, Karen; Cano, Noemi; Aerts, Dominique; Biot, Pierre; Casteleyn, Ludwine; Kolossa-Gehring, Marike; Schwedler, Gerda; Castaño, Argelia; Angerer, Jürgen; Koch, Holger M; Esteban, Marta; Schoeters, Greet; et al. (Environmental research. Section A, 2015)
A communication strategy was developed by The Consortium to Perform Human Biomonitoring on a European Scale (COPHES), as part of its objectives to develop a framework and protocols to enable the collection of comparable human biomonitoring data throughout Europe. The framework and protocols were tested in the pilot study DEMOCOPHES (Demonstration of a study to Coordinate and Perform Human biomonitoring on a European Scale). The aims of the communication strategy were to raise awareness of human biomonitoring, encourage participation in the study and to communicate the study results and their public health significance. It identified the audiences and key messages, documented the procedure for dissemination of results and was updated as the project progressed. A communication plan listed the tools and materials such as press releases, flyers, recruitment letters and information leaflets required for each audience with a time frame for releasing them. Public insight research was used to evaluate the recruitment material, and the feedback was used to improve the documents. Dissemination of results was coordinated in a step by step approach by the participating countries within DEMOCOPHES, taking into account specific national messages according to the needs of each country. Participants received individual results, unless they refused to be informed, along with guidance on what the results meant. The aggregate results and policy recommendations were then communicated to the general public and stakeholders, followed by dissemination at European level. Several lessons were learnt that may assist other future human biomonitoring studies. Recruitment took longer than anticipated and so social scientists, to help with community engagement, should be part of the research team from the start. As a European study, involving multiple countries, additional considerations were needed for the numerous organisations, different languages, cultures, policies and priorities. Therefore, communication documents should be seen as templates with essential information clearly indicated and the option for each country to tailor the material to reflect these differences. Future studies should consider setting up multidisciplinary networks of medical professionals and communication experts, and holding training workshops to discuss the interpretation of results and risk communication. Publicity and wide dissemination of the results helped to raise awareness of human biomonitoring to the general public, policy makers and other key stakeholders. Effective and timely communication, at all stages of a study, is essential if the potential of human biomonitoring research to improve public health is to be realised.
Keywords: vzorkové studie; Sampling Studies; Research Design; zdravotní politika; Europe; Program Development; monitorování životního prostředí; Community Participation; komunikace; lidé; Evropa; Focus Groups; Communication; rozvoj plánování; International Cooperation; Information Dissemination; Health Policy; Environmental Monitoring; zjišťování skupinových postojů; veřejná politika; mezinárodní spolupráce; Public Policy; účast komunity; výzkumný projekt; šíření informací; Humans